Pengembangan Sistem Informasi Proses Sidang berbasis Web pada Institut Agama Islam Negeri (IAIN) Padangsidimpuan - Abdul Yasir Halomoan; Buce Trias Hanggara; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Paperless system allows informations used to be viewed without unnecessary repetition of processes such as minor errors by users, staffs, or operators. State Institute for Islamic Studies Padangsidimpuan (IAIN) experienced problems precisely in the thesis defense registration process where minor errors occurred in the file checking process such as the lack of files and also the correctness of the files. To help the process of thesis defense registration, it is proposed to develop an information system for the process of thesis defense using a paperless system to reduce these errors from both staffs and students side. When developing the system, researcher uses the waterfall method, whis is a systematic and sequential development method starting from the requirement analysis stage, followed by design and implementation, then testing, and the last stage maintenance. Entering the testing stage, researcher is carried out by applying two different testing methods, which are black-box testing that is used to test the validity of the existing functions in the system and user acceptance testing that is used to test how mcuh user acceptance of the developed system. From the results of black-box testing using 5 testers, valid results were obtained. The same 5 people were also appointed to conduct testing using user acceptance testing, the testers answered 40 questions of 20 Functional Correctness and Completeness questions. 10 Usability questions, and 10 Confidentiality and Availability questions. Results from the answers of the testers were analyzed using Guttman Scale by looking at the percentage of â€œYesâ€ answers and obtained 100% results for each question given.